Integrasi Sistem Pengawasan Kesehatan Jembatan dengan Sistem Pengawasan Lalu Lintas - Muhammad Satria Wibawa; Achmad Irjik Ubay; Seno Adi Putra; Alvi Syahrina (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2020)
Bridge health monitoring system is a real-time data collection system that consists of components, responses, changes, and the construction process of bridge structures. This system aims to help assessing the structural security risks that could damage to the bridge structure by utilizing Wireless Sensor Network (WSN) as data retrieval. This system has a focus on the structure parameters of the bridge,but does not pay attention to vehicle factors,such as vehicle weight, vehicle patterns,and types of vehicles that pass on the bridge,whichcan also be factors of the bridge's health assessment. Anothersystem,namelya traffic control system,measuresvehicle weight using Weight in Motion (WIM).It can be used to obtainvehicle factors,especially vehicle weight,that also helps in assessing bridge health. This paper proposes the integrationof these two systems in order to create a system that can measure health of bridge structures,as well asmonitor the weight of the vehicle.Through this integration, it is possible to manage WSN sleep and wake time which helps saving energy.Experimental result shows that the system can measure natural frequencies close to the value of Finite Element Analysis (FEA),showing the validity of the developed system.